1997
DOI: 10.1084/jem.186.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Class I–restricted Cross-Presentation of Exogenous Self-Antigens Leads to Deletion of Autoreactive CD8+ T Cells

Abstract: In this report, we show that cross-presentation of self-antigens can lead to the peripheral deletion of autoreactive CD8+ T cells. We had previously shown that transfer of ovalbumin (OVA)-specific CD8+ T cells (OT-I cells) into rat insulin promoter–membrane-bound form of OVA transgenic mice, which express the model autoantigen OVA in the proximal tubular cells of the kidneys, the β cells of the pancreas, the thymus, and the testis of male mice, led to the activation of OT-I cells in the draining lymph nodes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
582
2
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 666 publications
(613 citation statements)
references
References 49 publications
28
582
2
1
Order By: Relevance
“…Male NOD mice, for example, show a stable periinsulitis that rarely progresses to IDDM. This fact is in line with reports showing that crosspresentation of peripheral antigens in general, and of antigens expressed as a transgene on beta cells in particular [36,37,38,39], could preferentially lead to the induction of tolerance rather than to autoimmunity. The parameters driving the decision between tolerance and immunity, that is, the transition from harmless insulitis to beta-cell killing, are still poorly understood.…”
Section: Discussionsupporting
confidence: 91%
“…Male NOD mice, for example, show a stable periinsulitis that rarely progresses to IDDM. This fact is in line with reports showing that crosspresentation of peripheral antigens in general, and of antigens expressed as a transgene on beta cells in particular [36,37,38,39], could preferentially lead to the induction of tolerance rather than to autoimmunity. The parameters driving the decision between tolerance and immunity, that is, the transition from harmless insulitis to beta-cell killing, are still poorly understood.…”
Section: Discussionsupporting
confidence: 91%
“…DC are now implicated in the regulation of the responses they initiate and in the maintenance of tolerance to self components [1,2]. DC are involved in both central tolerance in the thymus [3,4] and in peripheral tolerance of self-reactive T cells that have escaped intra-thymic deletion [2,[5][6][7]. The activation or 'maturation' state of the DC is believed to determine the balance between tolerance and immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of landmark studies, Heath and colleagues showed that the level of expressed protein, in their case OVA expressed under the rat insulin promoter (RIP), decides whether enough protein is ingested by DC to alert CD8 + CTL precursors for response induction (crosspriming) or tolerance induction (cross-tolerance), depending on the activation state of the DC [25]. In this model CTL priming depends on OVA-specific CD4 + T cells that need to activate the DC that are crosspresenting MHC class I peptides, to achieve crosspriming ("license to kill").…”
Section: The Importance Of Protein Levels and Protein Stability For Cmentioning
confidence: 99%
“…A large body of evidence shows that T cells die or become anergic if they do not receive these costimulatory and survival signals from DC [25,32,35,[56][57][58][59]. This is highly proper, because this places the DC in the middle of an intricate cellular network that ensures T cell death/anergy (in non-inflammatory conditions including most tumors) or survival (in the presence of dangerous pathogens).…”
Section: Mature DC Cross-prime Whereas Immature Dc Cross-tolerizementioning
confidence: 99%
See 1 more Smart Citation